David Hares stuff happens a dramatic journey of American war on Iraq - Salih, Elaff Ganim; Kaur, Hardev; Hassan, Mohamad Fleih (SciPress, 2016)
The war launched by America and its allies against the country of Iraq on 2003 was a debatable and notorious war for the public opinion was shocked with the realization that the reasons for launching the war under the title ‘Iraq’s Mass Destruction Weapons’ were false. The tragic consequences of this war led many writers around the world to question the policy of the United States and its manipulation of facts to justify their narratives. The present study examines the American policy of invading Iraq in David Hare’s Stuff Happens. It investigates Hare’s technique of combining documentary realism with imaginative reconstruction of the arguments to dramatize the American Invasion of Iraq. Stuff Happens is a historical and political play written as a verbatim theatre. It depicts the backroom deals and political maneuvers of the Bush administration in justifying their campaign against the ‘Axis of Evil’ culminated by the war against Iraq. The verbatim theatre is the best way of showing the gap between ‘what is said and what is seen to be done’. Scenes of direct speeches by real characters are part of this theatre dramatized to present a new reading of a historical event. In addition, characterization is used by Hare’s to chronicle the American war on Iraq. The study follows a postcolonial framework. The study concludes that Hare’s Stuff Happens succeeded in shaking the public opinion with the truth that Bush’s administration has manipulated facts in order to achieve their colonial and imperial interests in Iraq, which led to more destruction and violence in this country.